PENERAPAN MATEMATIKA PADA SISTEM PEMBAYARAN DISKRET DAN KONTINU ASURANSI KEMATIAN - Nuraeni, Gina; sunarsih, Sunarsih (MATEMATIKA, 2009)
As guarantee in a life insurance is which caused by death. The death results loss of income of someone or the family. With the result that, a life insurance provides a payment of specified amount upon the death of a given life. There are two systems in this payment, that the insurance payable at the moment of death (continuing insurance) and the insurance payable at the end of the year of death (discrete insurance). If life table are uniformly distributed, so there is a relationship that an immediate payment is equivalent on the average to a payment of Â at the end of the year of death. Â